DIAGNOSTIC AND TREATMENT OPTIONS IN AUTISTIC SPECTRUM DIDORDERS – AN OVERVIEW (Journal of Special Education and Rehabilitation, 2014)
Goal: To highlight the recent recommendations and future trends in diagnosing and managing autistic spectrum disorder.Methodology: Comprehensive search was done in the electronic database, journals, reference lists and dissertation related to the field.Results and conclusion: Autistic spectrum disorder is characterized by onset before the age of 3 years, qualitative impairment in social and communication skills along with repetitive behavioural pattern and restricted interests. Multiple pathways involving genetic, structural and environmental factors have been implicated in the etiopathogenesis. Diagnosis is primarily clinical, based on caregiver interview and observing the patient. However, certain biochemical, radiological and electrophysiological investigations are indicated in relevant scenarios. The mainstay of therapy is behavioural intervention with pharmacotherapy indicated for certain behavioural issues. Complementary and alternate treatment,   dietary   and   stem   cell   therapies are still investigational with some benefits.Various newer therapeutic options are currently being investigated, exploring the molecular and genetic basis of causation.
Keywords: Autistic spectrum disorder; DSM-V; Psychosocial interventions; Pharmacotherapy; Complementary and alternate treatment; mTOR inhibitors